2019
DOI: 10.1016/j.nicl.2019.101730
|View full text |Cite
|
Sign up to set email alerts
|

Structural brain correlates of fatigue in older adults with and without Parkinson's disease

Abstract: Fatigue is one of the most common and disabling nonmotor symptoms seen in Parkinson's disease (PD) and is also commonly seen in healthy older adults. Our understanding of the etiology of fatigue in older adults with or without PD is limited and it remains unclear whether fatigue in PD is specifically related to PD pathology. The objective of this study was thus to determine whether fatigue in PD was associated with structural changes in gray or white matter and explore whether these changes were similar in old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
23
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 77 publications
9
23
2
Order By: Relevance
“…Growing neuroimaging evidence in PD (e.g., Refs. [6][7][8][9]) revealed the involvement of nondopaminergic prefrontal-basal ganglia loops in fatigue, consistent with the presumed 'central' origin of fatigue [10].…”
Section: Introductionsupporting
confidence: 63%
“…Growing neuroimaging evidence in PD (e.g., Refs. [6][7][8][9]) revealed the involvement of nondopaminergic prefrontal-basal ganglia loops in fatigue, consistent with the presumed 'central' origin of fatigue [10].…”
Section: Introductionsupporting
confidence: 63%
“…These findings are in line with previous reports of cortical and subcortical atrophy pattern in PD and its relationship to motor severity (Zeighami et al, 2015;Fereshtehnejad et al, 2017). Nonmotor symptoms of PD have been linked to atrophy in the frontostriatal regions and limbic cortical and subcortical structures (Kostic et al, 2010;Reijnders et al, 2010;Carriere et al, 2014;van Mierlo et al, 2015;Vriend et al, 2016;Wee et al, 2016;Hanganu et al, 2017;Ye et al, 2018;Kluger et al, 2019). However, we found no significant correlation between the composite or individual nonmotor symptom scores and structural brain data.…”
Section: Discussionsupporting
confidence: 93%
“…A possible explanation for this discrepancy is that, unlike in most previous studies, our PD cohort as a whole did not have significant fatigue, apathy, depression, or anxiety. Moreover, we used a whole-brain approach, but not all previous reports were based on whole-brain structural data and focused on a limited number of regions selected a priori (Carriere et al, 2014;van Mierlo et al, 2015;Vriend et al, 2016;Wee et al, 2016;Kluger et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, human MRI studies reported that PD patients had reduced hippocampal volume and this was asymmetrical (with left hemisphere most affected) [268]. The dorsal striatum was also diminished in PD patients and this effect was exacerbated in patients with excessive fatigue [269]. In contrast, while we did find enlarged ventricular size, we did not find any reduction of volume in the nigrostriatal pathway or hippocampus.…”
Section: Figure 27contrasting
confidence: 80%